The Status of Women’s political empowerment worldwide (2017)
Measuring women’s political empowerment (WPE) poses an important challenge. Approaches to an empirical understanding of WPE are not thoroughly consolidated, thus preventing a comprehensive explanation of the status of women’s political empowerment globally. In this chapter, we contribute to the research on women’s political empowerment, adding a new dimension related to security and equality issues. We argue that to understand WPE globally, academic approaches must consider variables on the security status of women worldwide. To fill this gap, we developed a multivariable index using the Principal Component Analysis (PCA) as our main methodological strategy. The results provide researchers with inputs that will help explain women’s political empowerment through multidimensional components.